Participatory Action Research untuk Menyiapkan Model Students-Community Partnership pada Kemitraan Peningkatan Kesejahteraan Anak - Astrid Prameswari Lestari; Nuzulul Kusuma Putri (Media Gizi Kesmas, 2023)
Background: Surabaya is one of the largest cities located in East Java with population of around 2.874 million in 2022 (Central Agency on Statistics of East Java). It can cause many problems that can affect children's welfare in Surabaya such as the phenomenon of street children, juvenile delinquency, and the lack of guidance for children with social welfare problem. Unfortunately, this problem is not supported by the data collection of child problems in Surabaya. So that, solution is needed to solve this problem. Objectives: This community service called Spiritual Nurture Children (SNC) is aimed to (1) analyzing the potential of integrating student activities in partnership with practitioners to increase children's welfare, and (2) formulating the student-community partnership to increase children's welfare. Methods: The method is Participatory Action Research and Students-Community Partnership Model also used in integrating stakeholders to align the direction of the programs being carried out. This community service is carried out from June to September 2022 in 5 wards, there are Sidodadi, Simokerto, Tambakrejo, Tanah Kali Kedinding, and Bulak Banteng which is a supported area of Wahana Visi Indonesia. Results: The result of this community service is an increase in children's capacity in terms of spirituality and life skills as a first step to improve children's welfare. Conclusions: The community service Spiritual Nurture Children has been held in 16 times at all of the targeted area and reached the three outputs of this community service. Student-Community Partnership Model is used to integrate the whole stakeholders to equate the direction of programs. This community service can increase children's capacity in terms of spirituality and life skills to improve children's welfare. Evaluation is needed to improve the planning process to achieve better result in next year program.